Advancing Measurement and Research on Youths' Prosocial Behavior in the Digital Age. (9th January 2021) - Armstrong‐Carter, Emma; Telzer, Eva H.
Abstract: Widespread access to digital and social media has drastically altered the nature of youth's interpersonal connections. In this context, the opportunities children and adolescents have to help people around them are rapidly evolving. In this article, we review emerging literature on how digital media influences youth's prosocial development in new ways. Then we propose the next steps for advancing the field's understanding of youth's prosocial behavior in the digital age. We advocate for extending existing measures to capture experiences that are increasingly relevant for children and adolescents today, with a focus on current events, including the COVID‐19 pandemic, and social and political activism. We also provide a research agenda to advance the understanding of prosocial development.